Un organisme pour les artistes ou le milieu culturel? Représentation et institutionnalisation de la culture à Montréal. Issue 2 (4th May 2019) - Lussier, Martin
Abstract : Over the last 20 years, Montreal has been the site of significant administrative, economic, and cultural transformations. In this context, the artistic and cultural community has mobilized to defend its interests and intervene with decision makers. Central to this mobilization is a desire to set up an organization representative of 'culture' in Montreal. Two tendencies faced off against each other: on the one hand, artists wishing to promote culture as 'art, ' suggesting an organization of professional practitioners; on the other, a citizen movement proposing that all the citizens of the city have the same right to assert their voices on cultural issues. From the debates between the supporters of the two trends documented in local media, publications of the organizations as well as testimonies collected during interviews, this contribution focuses on the different ideas of culture and strategies of participation, as well as representations that led to the institutionalization of culture in Montreal.